Diagnostic accuracy of ultrasonography and mammography of breast lesions - Shrestha, Shreejana; Manandhar Dwa, Yogita; Jaiswal, Pooja; Karki, Prabhat; KC, Sudeep; Banjade, Udaya Raj (Journal of Patan Academy of Health Sciences, 2024)
Introduction: Breast cancer is the most common malignant tumors in women, with over one million cases diagnosed globally each year, resulting in approximately 410,000 deaths. Early detection and treatment significantly reduce the risk of mortality. Ultrasound and mammography are widely used non-invasive, cost-effective imaging techniques for early breast cancer diagnosis. This study aims to identify the characteristics of breast lesions on ultrasound and mammography and correlate them with histological findings. Method: This was a retrospective study conducted in Patan Hospital, with the data set from January 2019 to December 2022. All patient’s data were collected regarding findings of ultrasound, mammography, BIRADS from radiological department and correlated with histopathological diagnosis. All findings were compared for the sensitivity and specificity of mammography with ultrasonography in diagnosing breast lesions. Result: A total of 137 cases were found to have histopathology diagnosed benign and malignant breast lesions. Ultrasonography showed 91.58% sensitivity, 57.14% specificity, 82.86% positive predictive value, 75.00% negative predictive value, and 81.02% diagnostic accuracy. Mammography exhibited 92.63% sensitivity, 61.90% specificity, 84.62% positive predictive value, 78.79% negative predictive value, and 83.62% diagnostic accuracy. When combining mammography and ultrasonography, the results showed 93.63% sensitivity, 42.86% specificity, 78.76% positive predictive value, 75% negative predictive value, and 78.10% diagnostic accuracy. Conclusion: Ultrasound and mammography are both highly sensitive in detecting benign and malignant breast lesions. While mammography has a slightly higher overall accuracy in diagnosis, it is recommended to complement ultrasonography with mammography for a more comprehensive detection of breast lesions.